1999
DOI: 10.1016/s0039-6028(99)00713-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, surface core-level shifts and surface energy of the faceted GaAs(112)A and (1̄1̄2̄)B surfaces

Abstract: The GaAs(112)A and (1 :1 :2 :)B surfaces have been prepared by molecular-beam epitaxy (MBE ) and analyzed in situ by low-energy electron diffraction (LEED) and surface core-level spectroscopy of the Ga 3d and As 3d core levels using synchrotron radiation. The morphology of these surfaces has been studied in situ by scanning tunneling microscopy (STM ) and ex situ by scanning electron microscopy (SEM ) and atomic force microscopy (AFM ). Neither of the surfaces is stable, but both decompose into facets under st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…However, since the ridge contribution decreases as r -2 , we expect that the model including only the surface energy contributions will give accurate NW formation energies for all larger diameter zinc-blende nanowires. ZB {11-2} surfaces were found to be unstable [14] and indeed the NWs expected to have this facet orientation show instead tilted {111} microfacets [8]. In agreement with these experimental observations, we find a much higher formation energy for ZB NWs with {11-2} facets at all radii.…”
Section: Contributions To the Nanowire Formation Energysupporting
confidence: 86%
“…However, since the ridge contribution decreases as r -2 , we expect that the model including only the surface energy contributions will give accurate NW formation energies for all larger diameter zinc-blende nanowires. ZB {11-2} surfaces were found to be unstable [14] and indeed the NWs expected to have this facet orientation show instead tilted {111} microfacets [8]. In agreement with these experimental observations, we find a much higher formation energy for ZB NWs with {11-2} facets at all radii.…”
Section: Contributions To the Nanowire Formation Energysupporting
confidence: 86%
“…Platen and coworkers observed with LEED on the unstable GaAs(112)A surface facets with the orientation ͕124͖. 13,14 Lee et al examined the shape of three-dimensional InAs islands on GaAs͑001͒ with reflection high-energy electron diffraction ͑RHEED͒ and reported bounding facets corresponding to ͕136͖ planes. 16 Hasegawa et al characterized the same material system with STM and concluded that some of the sidewalls have the orientation ͕125͖.…”
mentioning
confidence: 99%
“…The first term, the free energy of the facets, is related to the surface atomic configuration and bonding structure that in particular for high index substrates, results on large area stable facets. [22] The edges energy, E edges , is related to the capillarity curvature. With the aim to calculate E edges in the review on spontaneous formation of periodically ordered nanometer-scale structures on crystal surfaces proposed by Shchukin, [21] the ideal situation where the corrugation is symmetric, is considered.…”
Section: Resultsmentioning
confidence: 99%